Temperatur dalam al-Qur’an; Tafsir Ilmi atas Kata al-Harr dan al-Bard (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2022)
Temperature in the Qur'an; Scientific Interpretation of the Words of al-Harr and al-Bard. The efforts to study Qur'an through a scientific approach are known as 'ilmi' interpretations. The Qur'an provides scientific cues in the discussion of verses regarding faith. In the Qur'an, the degree of hotness and coldness of an object is discussed in surah themes regarding the nature of heaven and hell, the creation of the jinn, fire, punishment (torment) and the trading habits of the Quraysh. The Qur'an uses word of al-harr for hot temperatures and al-bard for cold temperatures. Through the exploration of the meaning of the two words, this study seeks to reveal the scientific signs conveyed by the Qur'an in the discussion of temperature verses through the search for thematic interpretation methods. Some of the scientific cues obtained include: (1) each words expresses a different degree of temperature, (2) the word of al-harr refers to the peak of summer in Medina, (3) the phenomenon of cool flame (cold fire), and (4) water sources. Heat can be used as a treatment medium. The exposure of these signs does not show a contradiction between scienceand the Qur'an. On the other hand, it strengthens the purpose and function of the Qur'an as a guide for humans.